NUMERICAL ANALYSIS OF RICE GROWTH PHASES IN KARAWANG USING THE GAUSS-JORDAN ELIMINATION METHOD - Ruth Ririn Vania Siregar; Santri Chintia Purba; Bela Desy Natalia; Kornelius Anugrah Zebua (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
Indonesia's growth cannot be separated from Indonesia's economic growth. The agricultural sector has a massive and significant impact on Indonesia's economic growth. One of the agricultural products that’s important is rice. Rice is a seasonal crop that is very necessary for human survival. Karawang, one of the districts in West Java Province, which is known as Lumbung Padi City, is the location of the main topic in making this journal. In fact, based on BPS data, the area harvested for paddy fields in Karawang from 2010-2015 was found not to have increased regularly from year to year. This is interesting to discuss because the rice harvest area is expected to increase regularly to support Indonesia's economic growth. Of course, this is because the rice harvest area will affect the amount of rice produced in the rice fields. By ignoring other internal and external factors of rice growth, this journal will only focus on rice harvest area based on rice growth phases (vegetative 1, vegetative 2, and generative) and accumulated harvest area using the Gauss Jordan elimination method. Calculations are carried out to determine the possibility of farmers to predict the maximum amount of rice production and avoid losses in purchasing materials to support rice growth